Implementasi Model Pembelajaran Blanded Learning untuk Meningkatkan Motivasi Belajar Siswa - Istiqomah, Hascita (Tamaddun, 2025)
The purpose of this study was to determine how the implementation of the blanded learning model and the teacher’s efforts to increase student motivation in class IV B MI Nurul Islam. This type of research is qualitative research. The data sources in this study were teachers and students. The sample in this study were students of class IV B MI Nurul Islam. Data collection techniques used are observation, interview and documentation techniques. Meanwhile, the data analysis technique uses Miles and Huberman’s theory, which includes data reduction, display data and conclusion drawing. The results of this study indicate that blanded learning in class IV B is able to increase student learning motivation. With the implementation and efforts of the teacher in implementing blanded leraning being able to increase student learning motivation, increased student learning motivation can be seen when before learning with blanded learning students are not enthusiastic, tired, bored and lazy to take part in learning, in contrast to when learning using the blanded learning model students are more motivated, where students are more enthusiastic in learning, students are active in asking and answering questions then students always come on time and all students always adhere to health protocols.